2010
DOI: 10.1002/cncr.25219
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 trial of everolimus for metastatic renal cell carcinoma

Abstract: for the RECORD-1 Study Group BACKGROUND: A phase 3 trial demonstrated superiority at interim analysis for everolimus over placebo in patients with metastatic renal cell carcinoma (mRCC) progressing on vascular endothelial growth factor receptor-tyrosine kinase inhibitors. Final results and analysis of prognostic factors are reported. METHODS: Patients with mRCC (N ¼ 416) were randomized (2:1) to everolimus 10 mg/d (n ¼ 277) or placebo (n ¼ 139) plus best supportive care. Progression-free survival (PFS) and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

55
811
5
49

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,096 publications
(935 citation statements)
references
References 12 publications
55
811
5
49
Order By: Relevance
“…In pivotal phase III trials, bevacizumab, sunitinib, sorafenib, pazopanib, and temsirolimus have shown clinical benefit for patients with treatment-naïve or cytokine-pretreated RCC by prolonging progression-free or overall survival (temsirolimus only) times [8 -15]. Clinical benefit was observed in patients with metastatic RCC treated with everolimus as a second-line therapy after failure of sunitinib or sorafenib, as demonstrated by the more than double median progression-free survival time, compared with placebo [16,17].…”
mentioning
confidence: 99%
“…In pivotal phase III trials, bevacizumab, sunitinib, sorafenib, pazopanib, and temsirolimus have shown clinical benefit for patients with treatment-naïve or cytokine-pretreated RCC by prolonging progression-free or overall survival (temsirolimus only) times [8 -15]. Clinical benefit was observed in patients with metastatic RCC treated with everolimus as a second-line therapy after failure of sunitinib or sorafenib, as demonstrated by the more than double median progression-free survival time, compared with placebo [16,17].…”
mentioning
confidence: 99%
“…The VEGF gene, located at chromosome 6p12, consists of eight exons. mRNA splice variants involving exons 6 and 7 result in different VEGF isoforms, including VEGF 121 , VEGF 165 , VEGF 189. These isoforms have distinct matrix binding properties that modify their solubility and biological activity, of which VEGF 165 is the most abundant and biologically active [6].…”
Section: Vascular Endothelial Growth Factorsmentioning
confidence: 99%
“…Cleavage of VEGFA mRNA results in different VEGFA isoforms with distinct biological characteristics: VEGFA 121 , VEGFA 165 and VEGFA 189 . VEGFA 165 …”
Section: Vegfmentioning
confidence: 99%
See 1 more Smart Citation
“…HRQOL was evaluated with the EORTC QLQ-C30 and the FKSI-DRS before randomization, at day 1 of each cycle, and upon study discontinuation [25,34]. On the basis of an analysis of longitudinal mean scores on the EORTC QLQ-C30 and FKSI-DRS, HRQOL was sustained during everolimus therapy [25].…”
Section: Everolimusmentioning
confidence: 99%